FORMULASI DAN EVALUASI KRIM LIOFILISAT BUAH TOMAT (Solanum lycopersicum L) SEBAGAI PENINGKAT KELEMBABAN PADA KULIT - Nurul Arfiyanti Yusuf; Besse Hardianti; Ilmayani Dewi (LPPM - Universitas Muhammadiyah Banjarmasin, 2018)
Dry skin is defined to describe the loss or decrease in the moisture content of the stratum corneum (SC). Skin looks healthy if the outer layer contains 10% water. A research on the formulation and evaluation of tomato lyophilisate cream (Solanum lycopersicum L) has been done to improve moisture in the skin. The aim of this study is to know the physical stability of Tomato Fruit lyophilisate Cream formula (Solanum lycopersicum L) and to determine the concentration of tomato lyophilisate (Solanum lycorpersicum L) that is optimal for increasing moisture of the skin. Tomato lyophilisate had been conducted to formulate in M / A type cream. Tomato lyophilisate cream was evaluated physic stability and effectiveness as a moisturizer using skin analyzer intrument with 9 panelist. The results show that the physical stability evaluation test obtained formula 1, 2, and 3 is a stable formula. The results of the humidity test showed a persent increase in humidity in F1 (tomato 1% lyophilicat) is 11%, F2 (tomato 3% lyophilicates) is 22%, and F3 (5% tomato lithium phytate) is 39%. The best formula for improving moisture is formula III with an increase of 39% with a concentration of 5% tomato lithophilicity cream. Keyword : Cream, Tomato (Solanum lycopersicum L), Moisturizer.